(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The current UK system for recognizing learning and skills, formal and informal, no longer fits its purpose. It lags behind the needs of learners, employers, and policymakers, and contributes to persistent issues around skills gaps, economic inactivity, and low productivity. This presentation, based on the findings, and recommendations of the 2025 Digital Badging Commission (a partnership between Ufi VocTech Trust and the RSA), offered a bold, forward-looking vision: a nationally coordinated, interoperable digital badging infrastructure that can radically transform how we acknowledge and empower individual learning journeys in the UK. Drawing on extensive consultation, economic analysis, and international benchmarking, the Commission proposes a UK-wide ecosystem of trusted, verifiable digital credentials - digital badges - that make skills more visible, portable, and meaningful. These badges, embedded within formal education, lifelong learning, and workplace training, offer a way to articulate competencies that current qualifications often overlook, especially those gained in informal, semi-formal, and non-traditional contexts. The session will explore how digital badges can reflect granular, job-relevant capabilities that support inclusion, mobility, and motivation for all learners. At its core, the Commission’s work offers pragmatic, system-level answers to the challenge of opening recognition to all. Digital badges provide a scalable, technology-enabled way to make informal, and semi-formal learning visible, offering a "reliable companion" to open learning. By aligning digital badges with common quality frameworks and embedding them within national records and wallets, the UK can scale a trustworthy, inclusive digital credentialing system that responds to the real needs of learners and the economy. This presentation provided the Commission’s three key recommendations: Integrate Digital Badges into Formal Education: By embedding digital badges into post-16 education, vocational training, and the forthcoming Lifelong Learning Entitlement (LLE), the UK can support more agile, inclusive pathways through learning. Badges provide a mechanism to capture and reward functional, vocational, and transversal skills, supporting learner motivation, modular progression, and employer engagement. Mandate Open Technical Standards for Skills Wallets and Learner Records: To ensure interoperability and long-term sustainability, all digital credentials must adhere to open standards. The Commission calls for the formal digital education records (e.g. the DfE Education Record in England, My World of Work in Scotland) to adopt these standards, ensuring compatibility with emerging digital identity platforms and proprietary learner wallets, and empowering individuals to own and share their skills records across contexts. Establish a National Registry for Digital Credential Quality Assurance: Trust is the foundation of meaningful recognition. A national registry that houses shared standards and transparent frameworks will enable consistent quality, provide clear signals for employers, and support integration with formal systems. This registry will underpin the credibility of digital badges and make them usable at scale. Attendees gained insights into how the UK can leverage open recognition as a lever for inclusive growth, how digital badges can articulate skills across learning contexts, and how trust and infrastructure design are critical to adoption. By building shared standards, embedding badges within the formal system, and aligning recognition to economic needs, we can unlock the full potential of individuals, wherever, and however they learn. Keywords: digital badging, UK, 2025 Digital Badging Commission, digital badging infrastructure, learner wallets